A ZIF-8 / MXene@PDA composite lubricating material and preparation method thereof
By uniformly growing ZIF-8 nanoparticles on the MXene surface and generating polydopamine macromolecules, ZIF-8/MXene@PDA composites were constructed, which solved the problem of easy stacking and oxidation of MXene and ZIF-8 in solvents, and achieved good stability and excellent lubricating properties of the composites in water.
Patent Information
- Application Number
- CN202310754739.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-06-25
AI Technical Summary
Existing MXene and ZIF-8 nanocomposite lubricating materials are prone to layer stacking and oxidation in solvents, which affects the lubricating effect, and the stability and dispersion of ZIF-8 in aqueous solution are poor.
Small-layer Ti3C2 MXene nanosheets were prepared by acid etching and ultrasonic treatment, and ZIF-8 nanoparticles were grown in situ on the surface of MXene. Then, polydopamine macromolecules were generated on the surface through Michael addition reaction to construct ZIF-8/MXene@PDA composite material.
The composite material has good structural stability and excellent friction-reduction and anti-wear properties in water, while avoiding layered stacking and oxidation of MXene and ZIF-8, enhancing the lubrication effect.
Smart Images

Figure CN116804159B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials and relates to nanocomposite lubricating materials, and specifically relates to a ZIF-8 / MXene@PDA composite lubricating material and a preparation method thereof. Background Art
[0002] MXene is a typical two-dimensional material obtained by etching the surface or middle layer "A" element of the MAX phase. X atoms and M are arranged in layers. n+1 X n T x (n = 1, 2, 3 and 4) is the general structural formula of MXene, T x Typically represents the functional groups present on the surface after etching, including -O, -F, and -OH. MXenes possess a unique structure, good biocompatibility, and a rich array of active functional groups. Their excellent mechanical and tribological properties also lend them to excellent lubrication potential. MXene layers are connected by weak van der Waals forces, which facilitate interlayer shearing, providing low shear strength and reducing friction during sliding. However, etched and exfoliated nanosheets are susceptible to oxidation and prone to layered stacking in solvents, compromising their lubrication effectiveness.
[0003] ZIF-8 is a typical ZIFs with multiple metal sites, high crystallinity, good compatibility, and environmental friendliness. As an environmentally friendly organic-inorganic hybrid material, ZIF-8 can be deposited on the contact surface during friction to form an effective lubricating film. The organic-inorganic hybrid structure reduces the wrinkling effect caused by water friction. Adding ZIF-8 as a nanofiller to water can effectively fill the scratches generated during friction, significantly reducing the penetration path of corrosive substances, thereby effectively reducing corrosion. Therefore, ZIF-8 has great potential as a water-based lubricant additive. However, ZIF-8 has poor stability and dispersibility in aqueous solution, which leads to lubrication failure. Summary of the Invention
[0004] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a ZIF-8 / MXene@PDA composite lubricating material with stable structure and excellent friction reduction and anti-wear properties and a preparation method thereof.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a ZIF-8 / MXene@PDA composite lubricating material comprises the following steps:
[0007] Step 1: Place a polytetrafluoroethylene reaction bottle containing 20-40 mL of 12 mol / mL concentrated hydrochloric acid and 1.6-3.2 g of LiF in a 40-50 ° C oil bath, gradually add 1-2 g of Ti3AlC2 while slowly stirring, stir for 24-48 hours after the addition is completed, centrifuge and wash, then ultrasonicate for 1-3 hours, collect the supernatant by centrifugation and freeze-dry to obtain a few-layer Ti3C2 MXene powder;
[0008] Step 2: The Ti3C2 MXene powder prepared in step 1 was dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 1 to 4 mg / mL;
[0009] According to Zn 2+ The molar concentration ratio of Zn to Ti3C2 MXene is (1.5-3.5): 1. Add the zinc source to 25 mL of Ti3C2 MXene dispersion. 2+ The molar ratio of 2-methylimidazole to 2-methylimidazole was 1:8.7. 2-Methylimidazole was added to 25 mL of methanol, stirred for 30 minutes, and then the two were mixed. The mixed solution was stirred for 6 to 24 hours, washed by centrifugation, and freeze-dried to obtain ZIF-8 / MXene powder.
[0010] Step 3: Disperse 0.2 g of ZIF-8 / MXene powder synthesized in step 2 in 100 mL of tris buffer with a pH of 8-9, and ultrasonically disperse it for 0.5-1 hour. Take it out and shake it well every ten minutes. Then add dopamine hydrochloride at a mass ratio of ZIF-8 / MXene to dopamine hydrochloride of 1:(0.5-2). After vigorous stirring for 18-24 hours, centrifuge and wash it, and then freeze-dry it to obtain ZIF-8 / MXene@PDA powder.
[0011] The present invention also has the following technical features:
[0012] Preferably, the slow stirring in step 1 is stirring with a magnetic stirrer at a speed of 300 to 500 rpm.
[0013] Preferably, the centrifugal washing in step 1 is performed by centrifugal washing with dilute hydrochloric acid for 2 to 3 times, and then centrifugal washing with distilled water for 2 to 3 times.
[0014] Furthermore, the concentration of the dilute hydrochloric acid is 0.5 to 3 mol / mL.
[0015] Preferably, the zinc source in step 2 includes any one of Zn(C2O2H3)2·2H2O or Zn(NO3)2·6H2O.
[0016] Preferably, the stirring in step 1 and step 2 is carried out using a magnetic stirrer at a speed of 500 to 700 rpm.
[0017] Preferably, the centrifugal washing in step 2 is performed by centrifugal washing with methanol 3 times.
[0018] Preferably, the vigorous stirring in step 3 is performed using a magnetic stirrer at a speed of 700 to 900 rpm.
[0019] Preferably, the centrifugal washing in step 3 is performed by centrifugal washing twice with ethanol and then centrifugal washing once with distilled water.
[0020] The present invention also protects a ZIF-8 / MXene@PDA composite lubricating material prepared by the method described above.
[0021] Compared with the prior art, the present invention has the following technical effects:
[0022] The present invention uses acid etching and ultrasonic treatment to prepare a few-layer Ti3C2 MXene nanosheets as a carrier, and then uniformly grows ZIF-8 nanoparticles on the MXene surface in situ. The growth process is simple and does not require high temperature and high pressure. The ZIF-8 nanoparticles are uniformly anchored on the MXene surface, which not only avoids the layered stacking of MXene nanosheets but also inhibits the agglomeration of the nanoparticles themselves. Finally, a layer of polydopamine macromolecules is generated on the ZIF-8 / MXene surface through a Michael addition reaction to construct a ternary ZIF-8 / MXene@PDA composite material. The polydopamine on the surface has the function of preventing MXene oxidation and ZIF-8 hydrolysis. The synergistic lubrication effect of the various components of the composite material helps to achieve low friction and wear. The prepared ZIF-8 / MXene@PDA composite material has good structural stability in water and exhibits excellent friction reduction and anti-wear properties as a water-based lubricating additive. The lubricating material also has good environmental compatibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is an SEM image of the few-layer MXene prepared in Example 1 of the present invention;
[0024] Figure 2 is a SEM image of ZIF-8 / MXene prepared in Example 1 of the present invention;
[0025] Figure 3 is an SEM image of the ZIF-8 / MXene@PDA composite lubricating material prepared in Example 1 of the present invention;
[0026] Figure 4 is the XRD of the ZIF-8 / MXene material prepared in Example 1 of the present invention;
[0027] Figure 5 This is the Raman spectrum of the ZIF-8 / MXene@PDA composite lubricating material prepared in Example 1 of the present invention;
[0028] Figure 6 This is the friction coefficient curve of the ZIF-8 / MXene@PDA composite lubricating material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The specific contents of the present invention are further explained in detail below with reference to the embodiments.
[0030] Example 1
[0031] Step 1: Place a polytetrafluoroethylene reaction bottle containing 20 mL of 12 mol / mL concentrated hydrochloric acid and 1.6 g of LiF in an oil bath at 45 ° C, gradually add 1 g of Ti3AlC2 while slowly stirring at 300 rpm, and stir at 500 rpm for 24 hours after the addition is completed. After stirring, centrifuge and wash with 1 mol / mL dilute hydrochloric acid three times, then centrifuge and wash with distilled water twice, and ultrasonicate for 2 hours. After that, the supernatant is collected by centrifugation and freeze-dried to obtain a few-layer Ti3C2 MXene powder;
[0032] Step 2: The Ti3C2 MXene powder prepared in step 1 was dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 3 mg / mL;
[0033] According to Zn 2+ The molar concentration ratio of Zn(C2O2H3)2·2H2O to Ti3C2 MXene was 1.5:1. 0.147 g of Zn(C2O2H3)2·2H2O was added to 25 mL of Ti3C2 MXene dispersion. 2+ The molar ratio of 2-methylimidazole to 2-methylimidazole was 1:8.7. 2-Methylimidazole was added to 25 mL of methanol, stirred for 30 minutes, and then the two were mixed. After the mixed solution was stirred at 500 rpm for 12 hours, it was centrifuged and washed three times with methanol, and freeze-dried to obtain ZIF-8 / MXene powder.
[0034] Step 3: Disperse 0.2 g of the synthesized ZIF-8 / MXene powder in 100 mL of tris buffer with a pH of 8.5, and ultrasonically disperse it for 0.5 h. Take it out and shake it every ten minutes. Then add an equal mass of dopamine hydrochloride. After vigorously stirring at 700 rpm for 24 hours, centrifuge and wash it twice with ethanol and once with distilled water. After freeze-drying, ZIF-8 / MXene@PDA powder was obtained.
[0035] The material prepared in Example 1 was tested. The SEM image of the few-layer MXene prepared in Example 1 is as follows: Figure 1 As shown in Figure 2, MXene exhibits a typical thin-layered flake shape rather than the original block and accordion shape.
[0036] The SEM image of ZIF-8 / MXene prepared in Example 1 is as follows: Figure 2 As shown in Figure 2, ZIF-8 nanoparticles are uniformly grown on the MXene surface.
[0037] The SEM image of the ZIF-8 / MXene@PDA composite lubricating material prepared in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that the surface of the ZIF-8 / MXene@PDA composite lubricating material prepared by the present invention is smooth, and no ZIF-8 nanoparticles are observed. This is due to the polydopamine coating on its surface.
[0038] The XRD pattern of ZIF-8 / MXene prepared in Example 1 is as follows: Figure 4 As shown. For Ti3AlC2, the peaks at 9.4°, 19°, 38.6° and 60° correspond to the (002), (004), (104) and (110) planes of MXene. However, the characteristic peak corresponding to (104) is not found in the XRD spectrum of MXene, and the characteristic peaks representing (002) and (004) are shifted to a lower 2θ angle. According to the Bragg equation, the interplanar spacings of MAX phase and MXene (002) are and The increase in interplanar spacing is due to acid etching of the "Al" layer in Ti3AlC2, confirming the transformation of Ti3AlC2 to Ti3C2 MXene. The XRD patterns of ZIF-8 / MXene and ZIF-8 are similar, indicating that anchoring to the surface of MXene nanosheets does not affect the crystal structure of ZIF-8.
[0039] The Raman spectrum of the ZIF-8 / MXene@PDA composite lubricating material prepared in Example 1 is as follows: Figure 5 As shown. MXene is located at 197 cm -1 The peaks correspond to A1g (Ti, C, and O), representing the out-of-plane vibration of MXene, 385 cm -1 The peak at is attributed to the groups interacting with Ti atoms (T x ) in-plane vibration, 600 cm -1The broad peak at is attributed to carbon vibration. Generally speaking, ID / IG represents the degree of defects in carbon materials, with larger values indicating greater defects. Compared to MXene, the ID / IG of ZIF-8 / MXene increases to 0.98, due to the embedding of ZIF-8 into the interlayers of MXene, which increases the defects in the MXene. In contrast, the ID / IG does not change significantly after the introduction of PDA, demonstrating that the surface-adhered polydopamine molecular layer does not cause changes in the composite's defects.
[0040] The friction coefficient curve of the ZIF-8 / MXene@PDA composite lubricant prepared in Example 1 as an ethylene glycol aqueous solution (EGaq) additive is as follows: Figure 6 As shown. Figure 6 It can be seen that compared with pure water and single-component lubricants and additives, ZIF-8 / MXene@PDA exhibits the lowest friction coefficient, with an average friction coefficient as low as 0.11, which is 78% lower than that of pure water.
[0041] Example 2
[0042] Step 1: Place a polytetrafluoroethylene reaction bottle containing 30 mL of 12 mol / mL concentrated hydrochloric acid and 1.92 g of LiF in an oil bath at 40 ° C, and gradually add 1.2 g of Ti3AlC2 while slowly stirring at 500 rpm. After the addition is completed, stir at 600 rpm for 30 hours. After stirring, centrifuge and wash three times with 0.5 mol / mL dilute hydrochloric acid, then centrifuge and wash three times with distilled water, and ultrasonicate for 1 hour. After that, the supernatant is collected by centrifugation and freeze-dried to obtain a few-layer Ti3C2 MXene powder;
[0043] Step 2: The Ti3C2 MXene powder prepared in step 1 was dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 1 mg / mL;
[0044] According to Zn 2+ The molar concentration ratio of Zn(C2O2H3)2·2H2O to Ti3C2 MXene is 2:1. 0.065 g of Zn(C2O2H3)2·2H2O is added to 25 mL of Ti3C2 MXene dispersion. 2+ 2-Methylimidazole was added to 25 mL of methanol at a molar ratio of 1:8.7, and the two were mixed after stirring for 30 minutes. The mixed solution was stirred at 600 rpm for 6 hours, washed three times by centrifugation with methanol, and freeze-dried to obtain ZIF-8 / MXene powder.
[0045] Step 3: Disperse 0.2 g of the synthesized ZIF-8 / MXene powder in 100 mL of tris buffer with a pH of 9, ultrasonically disperse it for 1 hour, take it out and shake it every ten minutes, then add 0.4 g of dopamine hydrochloride, vigorously stir it at 900 rpm for 18 hours, centrifuge and wash it twice with ethanol, then centrifuge and wash it once with distilled water, and then freeze-dry to obtain ZIF-8 / MXene@PDA powder.
[0046] Example 3
[0047] Step 1: Place a polytetrafluoroethylene reaction bottle containing 40 mL of 12 mol / mL concentrated hydrochloric acid and 3.2 g of LiF in an oil bath at 40 ° C, gradually add 2 g of Ti3AlC2 while slowly stirring at 400 rpm, and stir at 700 rpm for 36 hours after the addition is completed. After stirring, centrifuge and wash twice with 3 mol / mL dilute hydrochloric acid, then centrifuge and wash twice with distilled water, and ultrasonicate for 3 hours. After that, the supernatant is collected by centrifugation and freeze-dried to obtain a few-layer Ti3C2 MXene powder;
[0048] Step 2: The Ti3C2 MXene powder prepared in step 1 was dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 4 mg / mL;
[0049] According to Zn 2+ The molar concentration ratio of Zn(C2O2H3)2·2H2O to Ti3C2 MXene is 3:1. 0.391 g of Zn(C2O2H3)2·2H2O is added to 25 mL of Ti3C2 MXene dispersion. 2+ The molar ratio of 2-methylimidazole to 2-methylimidazole was 1:8.7. 2-Methylimidazole was added to 25 mL of methanol, stirred for 30 minutes, and then the two were mixed. After the mixed solution was stirred at 700 rpm for 18 hours, it was centrifuged and washed three times with methanol, and freeze-dried to obtain ZIF-8 / MXene powder.
[0050] Step 3: Disperse 0.2 g of the synthesized ZIF-8 / MXene powder in 100 mL of tris buffer with a pH of 8, ultrasonically disperse for 0.6 hours, take it out and shake it every ten minutes, then add 0.1 g of dopamine hydrochloride, vigorously stir it at 800 rpm for 20 hours, centrifuge and wash it twice with ethanol, then centrifuge and wash it once with distilled water, and then freeze-dry to obtain ZIF-8 / MXene@PDA powder.
[0051] Example 4
[0052] Step 1: Place a polytetrafluoroethylene reaction bottle containing 30 mL of 12 mol / mL concentrated hydrochloric acid and 2.5 g of LiF in an oil bath at 50 ° C, and gradually add 1.56 g of Ti3AlC2 while slowly stirring at 300 rpm. After the addition is completed, stir at 300 rpm for 48 hours. After stirring, centrifuge and wash with 2 mol / mL dilute hydrochloric acid three times, then centrifuge and wash with distilled water twice, and ultrasonicate for 2 hours. After that, the supernatant is collected by centrifugation and freeze-dried to obtain a few-layer Ti3C2 MXene powder;
[0053] Step 2: The Ti3C2 MXene powder prepared in step 1 was dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 2 mg / mL;
[0054] According to Zn 2+ The molar concentration ratio of Zn(NO3)2·6H2O to Ti3C2 MXene is 3.5:1. 0.228 g of Zn(NO3)2·6H2O is added to 25 mL of Ti3C2 MXene dispersion. 2+ The molar ratio of 2-methylimidazole to 2-methylimidazole was 1:8.7. 2-Methylimidazole was added to 25 mL of methanol, stirred for 30 minutes, and then the two were mixed. After the mixed solution was stirred at 500 rpm for 24 hours, it was centrifuged and washed three times with methanol, and freeze-dried to obtain ZIF-8 / MXene powder.
[0055] Step 3: Disperse 0.2 g of the synthesized ZIF-8 / MXene powder in 100 mL of tris buffer with a pH of 8.5, and ultrasonically disperse it for 0.8 hours. Take it out and shake it every ten minutes. Then add 0.3 g of dopamine hydrochloride. After vigorously stirring at 700 rpm for 24 hours, centrifuge and wash it twice with ethanol, and then centrifuge and wash it once with distilled water. After freeze-drying, ZIF-8 / MXene@PDA powder was obtained.
[0056] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present invention.
Claims
1. A method for preparing a ZIF-8 / MXene@PDA composite lubricating material, characterized in that: The following steps are involved: Step 1: Place a polytetrafluoroethylene reaction bottle containing 20-40 mL 12 mol / mL concentrated hydrochloric acid and 1.6-3.2 g LiF in a 40-50 ° C oil bath, gradually add 1-2 g Ti3AlC2 under slow stirring, stir for 24-48 hours after the addition, centrifuge and wash after the stirring is completed, then ultrasonicate for 1-3 hours, collect the supernatant by centrifugation and freeze-dry to obtain a few-layer Ti3C2 MXene powder; Step 2: The Ti3C2 MXene powder prepared in step 1 is dispersed in water and crushed for 30 minutes to obtain a Ti3C2 MXene dispersion with a concentration of 1 to 4 mg / mL; According to Zn 2+ The molar concentration ratio of Zn to Ti3C2 MXene is (1.5-3.5):
1. Add the zinc source to 25 mL of Ti3C2 MXene dispersion. 2+ The molar ratio of 2-methylimidazole to 2-methylimidazole was 1:8.
7. 2-Methylimidazole was added to 25 mL of methanol, and the two were mixed after stirring for 30 minutes. The mixed solution was stirred for 6 to 24 hours, centrifuged and washed, and freeze-dried to obtain ZIF-8 / MXene powder. Step 3: Disperse 0.2 g of ZIF-8 / MXene powder synthesized in step 2 in 100 mL of tris buffer with a pH of 8 to 9, and ultrasonically disperse for 0.5 to 1 hour. Take it out and shake it well every ten minutes. Then add dopamine hydrochloride at a mass ratio of ZIF-8 / MXene to dopamine hydrochloride of 1:(0.5 to 2). After vigorous stirring for 18 to 24 hours, centrifuge and wash, and obtain ZIF-8 / MXene@PDA powder after freeze-drying.
2. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The slow stirring in step 1 is stirring with a magnetic stirrer at a rotation speed of 300 to 500 rpm.
3. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The centrifugal washing in step 1 is performed by centrifugal washing with dilute hydrochloric acid for 2 to 3 times, and then centrifugal washing with distilled water for 2 to 3 times.
4. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 3, characterized in that: The concentration of the dilute hydrochloric acid is 0.5-3 mol / mL.
5. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The zinc source described in step 2 includes any one of Zn(C2O2H3)2·2H2O or Zn(NO3)2·6H2O.
6. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The stirring in step 1 and step 2 is carried out by using a magnetic stirrer at a rotation speed of 500 to 700 rpm.
7. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The centrifugal washing described in step 2 is centrifugal washing with methanol for 3 times.
8. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The vigorous stirring described in step 3 is stirring with a magnetic stirrer at a rotation speed of 700 to 900 rpm.
9. The method for preparing the ZIF-8 / MXene@PDA composite lubricating material according to claim 1, characterized in that: The centrifugal washing described in step 3 is to use ethanol for two centrifugal washings and then use distilled water for one centrifugal washing.
10. A ZIF-8 / MXene@PDA composite lubricating material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
ZIF-67@MXene composite material as well as preparation method and application thereof
CN112680746A
Method for detecting 5-formyl cytosine deoxyribonucleotide by bismuth sulfide-MXene-based photoelectrochemical sensor
CN114295699A